Rasch modelling approach to measure the quality of algebraic thinking test item for junior high school students - Rusyid, Husnul Khatimah; Suryadi, Didi; Herman, Tatang; Adnan, Mazlini; Lutfi, Ahmad; Mukhibin, Ahmad (Beta: Jurnal Tadris Matematika, 2024)
[English]: The importance of conducting this research is due to the lack of valid and reliable assessment tools for evaluating students’ algebraic thinking ability within the context of the Indonesian school curriculum. This study aims to describe the quality of algebraic thinking test items for linear equation topics. The research procedure involves three main phases, i.e., developing the test item, conducting a sample trial, and examining the quality of the test item through Rasch model analysis. The test instrument developed in this study consists of six essay questions, each representing an indicator of algebraic thinking skill. The test instrument was then used to collect quantitative data from 37 junior high school students selected as research respondents through a purposive sampling technique. The Rasch analysis was assisted by Ministep software. The research results show that all items fall into the valid category with a reliability index of 0.81, and so the test instrument is declared to have good quality. Analysis of the item difficulty level revealed that two items fell into the difficult category, one item was difficult, one item was moderate, one item was easy, and one item was very easy. Overall, the algebraic thinking ability test instrument developed in this study has met the Rasch modelling assumption, despite the fact that some items need to be revised. The instrument can be utilized by the teacher to evaluate the students’ algebraic thinking skills in mathematics learning, specifically for linear equation topics. [Bahasa]: Minimnya instrument tes kemampuan berpikir aljabar yang valid serta reliabel dalam konteks kurikulum sekolah di Indonesia menjadikan penelitian ini penting untuk dilakukan. Penelitian ini bertujuan untuk mendeskripsikan kualitas instrumen tes berpikir aljabar pada materi persamaan garis lurus. Prosedur penelitian meliputi tiga fase utama, yaitu pengembangan butir soal, ujicoba pada sampel terbatas, dan analisis kualitas butir soal melalui analisis model Rasch. Instrumen tes yang dikembangkan berupa 6 soal essai, di mana masing-masing soal mewakili indikator kemampuan berpikir aljabar. Instrument tes selanjutnya digunakan untuk mengumpulkan data kuantitatif dari 37 siswa SMP yang dipilih sebagai responden penelitian melalui teknik purposive sampling. Analisis Rasch dilakukan dengan bantuan aplikasi Ministep. Hasil penelitian menunjukkan bahwa semua soal masuk dalam kategori valid dengan indeks reliabilitas sebesar 0.81, sehingga dapat dikatakan instrument tes memiliki kualitas yang baik. Analisis tingkat kesulitan soal mengungkapkan bahwa 2 item masuk dalam kategori sangat sulit, 1 item sulit, 1 item sedang, 1 item mudah, dan 1 item sangat mudah. Secara keseluruhan, instrumen kemampuan berpikir aljabar yang dikembangkan memenuhi kriteria pemodelan Rasch meskipun terdapat beberapa item soal yang perlu direvisi. Instrumen ini dapat dimanfaatkan oleh guru sebagai alat penilaian dalam mengevaluasi kemampuan berpikir aljabar siswa pada pembelajaran matematika, khususnya untuk materi persamaan linear